Influencing factors of on autogenous arteriovenous fistula thrombus in maintenance hemodialysis patients - YANG Ling; LIU Bin; YU Jun-chao; JIANG Xiao-lan; MIN Rui; WANG Bang-bin; LI Xue-hua; SUN Yan-ling; LIU Ai-min (Linchuang shenzangbing zazhi)
Objective To observe whether plasma homocysteine(Hcy),c-reactive protein(CRP) level and incidence of dialysis hypotension and other indicators influence the onset of autogenous arteriovenous internal fistula(AVF) thrombus in the maintenance hemodialysis(MHD) patients.Methods Nine-two cases of MHD patients with AVF vascular access were chosea The thrombus event of one time or over within one year was observed.The patients were divided into AVF thrombosis group and AVF non-thrombus group.The incidence of hypotension in dialysis,the average levels of Hcy,CRP,low density lipoprotein cholesterol(LDL-c),plasma albumin,hemoglobin(Hb),hematocrit(HCT) and ferritin by two tests within one year,and duration of dialysis were compared between two groups.The associated risk factors were analyzed.Results The incidence of dialysis hypotension in the 92 MHG patients was 19.6%(18/92).There was significant difference in the incidence of hypotension in dialysis between AVF thrombus group and AVF non-thrombosis group(P<0.05).The incidence of abnormal level of Hcy in 92 MHD patients was 100%,but there was no statistically significant difference in plasma Hcy levels between the two groups.There was no significant difference in CRP and ferritin levels between two groups.Hb and hypotension in dialysis were the risk factors for AVF thrombosis The duration of dialysis in AVF thrombus group(months) was significantly shorter than in AVF non-thrombus group(P<0.05).The HCT in AVF thrombus group was significantly lower than in AVF non-thrombus group(P<0.05).There were no significant differences in other indexes,such as white blood cells,SCr,platelets,LDL,Alb between two groups.Conclusions The hypotension in dialysis and Hb are the risk factors for AVF thrombosis in MHD patients,and Hcy and CRP are not correlated with occurrence of AVF thrombosis.